Asymptotic method in two-dimensional problems of electroelasticityі - Shporta, A.; Шпорта, Анна Григорівна; Kagadiy, T.; Кагадій, Тетяна Станіславівна; Onopriienko, O.; Онопрієнко, Олег Дмитрович (Національний ТУ «Дніпровська політехніка», 2020)
Generalization of the asymptotic method for solving two¬dimensional problems of electroelasticity. Accounting for electric charges arising from deformation on the surfaces of piezoelectric materials. Checking the possibility of taking into account the magnetic field and the opposite effect when exposed to an electric field. Methodology. The mathematical model of the piezoelectric material is described using the equilibrium equations, the electroelastic state, and the Cauchy relations. A small parameter is introduced as a ratio of the physical characteristics of the material. Transformations of coordinates and desired functions depending on the specified parameter are proposed. findings. The introduction of these transformations allowed splitting the initial boundary¬value problem into two components with different properties. Each of them contains both mechanical and electrical components. The solution is sought as a superposition of solutions of both types. Each of the types of stress¬strain states contains the main function and an auxiliary one. The expansion of the desired functions in rows by parameter e and the construction of asymptotic sequences lead to the fact that in each approximation the main functions are sought from the Laplace or Poisson equations. Auxiliary ones are found by integration. The analysis of the boundary conditions is given. It is shown that they can almost always be formulated for basic functions. originality. The method proposed earlier by the authors for reducing the boundary value problems of linear and nonlinear elasticity theory to the sequential solution of potential theory problems is generalized for the case of modern piezoelectric materials described by electroelasticity equations. Practical value. With the help of the proposed approach, analytical solutions of practically important problems of electroelasticity can be obtained; estimates of the stress¬strain state of products from piezoelectric materials are carried out. The results can be used as null approximations in numerical calculations. Узагальнення асимптотичного методу для розв’язання двовимірних задач електропружності. Урахування електричних зарядів, що виникають під час деформації на поверхнях п’єзоелектричних матеріалів. Перевірка можливості врахування магнітного поля та оберненого ефекту під впливом електричного поля. Методика. Математична модель п’єзоелектричного матеріалу описана за допомогою рівнянь рівноваги, електропружного стану та співвідношень Коші. Уведено малий параметр як співвідношення фізичних характеристик матеріалу. Запропоновані перетворення координат і невідомих функцій, що залежать від вказаного параметру. Результати. Уведення вказаних перетворень дозволило розщепити вихідну крайову задачу на дві складові з різноманітними властивостями. Кожна з них містить як механічну, так і електричну компоненту. Розв’язок відшукують у вигляді суперпозиції розв’язків обох типів. Кожен із типів напружено¬деформованих станів містить основну функцію та допоміжну. Розклад шуканих функцій у ряди за параметром e та побудова асимптотичних послідовностей призводить до того, що в кожному наближенні основні функції розшукуються з рівнянь Лапласа або Пуассона. Допоміжні знаходять інтегруванням. Проведено аналіз граничних умов. Показано, що вони практично завжди можуть бути сформульовані для основних функцій. Наукова новизна. Запропонований раніше авторами метод зведення крайових задач лінійної та нелінійної теорії пружності до послідовного розв’язання задач теорії потенціалу узагальнений для випадку сучасних п’єзоелектричних матеріалів, що описані рівняннями рівноваги електропружності. Практична значимість. За допомогою запропонованого підходу можуть бути отримані аналітичні розв’язки практично важливих задач електропружності, проведені оцінки напружено¬деформованого стану виробів із п’єзоелектричних матеріалів. Результати можуть бути використані як нульові наближення при чисельних розрахунках.
Асимптотичний метод у двомірних задачах електропружності
Keywords: electroelasticity; електропружність; interaction; взаємодія; analytical solution; аналітичний розв’язок; piezoelectric; п’єзоелектричний; asymptotic method; асимптотичний метод; two-dimensional problems; двовимірні задачі; piezoelectromagnetic elements; п’єзоелектромагнітні елементи